PEMANFAATAN KULIT BUAH NAGA MERAH DALAM PEMBUATAN PERMEN JELLY BUAH PEDADA - sulistianingsih, Yuni; Johan, Vonny Setiaries; Herawati, Netti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research carried to obtain the best ratio of red dragon fruit peel and pedada fruit extracts in the manufacture of jelly candy. The research used a Complete Randomized (CRD) with five treatments and four replications which were followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research were PN1(ratio of red dragon fruit peel and pedada fruit extracts 90:10), PN2 (ratio of red dragon fruit peel and pedada fruit extracts 80:20), PN3 (ratio of red dragon fruit peel and pedada fruit extracts 70:30), PN4 (ratio of red dragon fruit peel and pedada fruit extracts 60:40), PN5 (ratio of red dragon fruit peel and pedada fruit extracts 50:50). The result of analysis showed that the ratio of red dragon fruit peel and pedada fruit extracts significantly effect on moisture content, ash content, fiber content, reduce sugar and colour but did not significantly effect of taste, texture and overall assesment of jelly candy. The best formulation jellycandy was PN4 with water content 7.52%; ash content 2.02%; fiber content 1.60% and reduce sugar content 20.48%. Organoleptic scores of PN4 were 2.37 (red); 3.07 (sweet little sour); 3.46 (netral flavour); 3.93 (chewy) and 3.70 (overall) assesment of jelly candy. Keyword:Jelly candy, red dragon fruit peel and pedada fruit.